2014
DOI: 10.1021/nn501996a
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrodes Based upon Mo:BiVO4 Inverse Opals for Photoelectrochemical Water Splitting

Abstract: BiVO4 has been regarded as a promising material for photoelectrochemical water splitting, but it suffers from a major challenge on charge collection and utilization. In order to meet this challenge, we design a nanoengineered three-dimensional (3D) ordered macro-mesoporous architecture (a kind of inverse opal) of Mo:BiVO4 through a controllable colloidal crystal template method with the help of a sandwich solution infiltration method and adjustable post-heating time. Within expectation, a superior photocurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
198
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(203 citation statements)
references
References 50 publications
(100 reference statements)
4
198
0
1
Order By: Relevance
“…For example, Zhou et al demonstrated enhancement in the photocurrent density and photoelectrochemical water splitting efficiency for 3D ordered macroporous Mo:BiVO 4 inverse opal structures as compared to the porous but disordered counterpart (Figure 26). 25 This enhancement was attributed to the synergistic effects of compositional and structural optimization, leading to an improvement in charge transport properties. 25 Reproduced with permission from the American Chemical Society.…”
Section: Factors Influencing Cbpm Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhou et al demonstrated enhancement in the photocurrent density and photoelectrochemical water splitting efficiency for 3D ordered macroporous Mo:BiVO 4 inverse opal structures as compared to the porous but disordered counterpart (Figure 26). 25 This enhancement was attributed to the synergistic effects of compositional and structural optimization, leading to an improvement in charge transport properties. 25 Reproduced with permission from the American Chemical Society.…”
Section: Factors Influencing Cbpm Catalystsmentioning
confidence: 99%
“…25 This enhancement was attributed to the synergistic effects of compositional and structural optimization, leading to an improvement in charge transport properties. 25 Reproduced with permission from the American Chemical Society.…”
Section: Factors Influencing Cbpm Catalystsmentioning
confidence: 99%
“…In general, the increase of charge carrier density is associated with increased electrical conductivity (σ) of the photoelectrode, which is given by σ=en”, where e, n and ” are the electronic charge, the concentration and mobility of charge carrier, respectively. A high mobility is highly favorable for improving charge separation and transport [43,45].…”
Section: Photoelectrochemical Studies Of Mos 2 Cds and Mos 2 /Cds Nmentioning
confidence: 99%
“…13 Doping by introducing an extrinsic defect through the addition of a transition-metal cation or an anion can increase the carrier density and thus improve the conductivity for optimum photocatalytic performance. Following 4 this strategy, numerous studies and research efforts have been focused on doping BiVO 4 with Mo and W. [14][15][16][17] This effect has been extended as well to intrinsic doping defined as native defects. Some studies suggested that this oxide can be stoichiometric at 1 atmospheric oxygen pressure, while oxygen vacancies might be created in reducing conditions.…”
Section: Introductionmentioning
confidence: 99%